Exploring perceptions of digital and printed texts in EFL reading comprehension among Vietnamese secondary students and teachers - Huỳnh, Mỹ Tiên (Trường Đại học Trà Vinh; Trà Vinh, 2024)
The purposes of this research are to investigate Vietnamese secondary students’ perceptions of using digital and printed texts in reading comprehension and explore how Vietnamese secondary teachers perceive the use of digital and printed texts in teaching English reading comprehension.